Implementation of Problem-Based Learning Model in State Senior High School 4, Gorontalo City - Nggilu, Ariyanto; Ngiu, Zulaecha; Hamim, Udin; Wantu, Asmun W. (Universitas Negeri Gorontalo, 2025)
In Senior High School 4, Gorontalo City, there are several teachers who only use the lecture model in class when teaching, which creates a mediocre learning atmosphere, as a result, students' enthusiasm for learning decreases. Teachers do not yet understand how to design and implement learning models effectively. Inconsistency of Learning Models with Student Characteristics, Minimal Student Engagement in learning, because learning is only centered on teachers, Lack of Teacher Understanding of Learning Models, Evaluations that are not in line with Learning Models, and there are still many evaluations that only focus on memorization, whereas an effective learning model that can increase students' learning motivation is a learning model that emphasizes students' critical thinking skills. The method used in this study is Qualitative. The results and discussion of this study are In general, the implementation of Problem Based Learning has a significant positive impact on students' learning motivation, especially in terms of increasing involvement, self-confidence, and collaborative learning. However, the success of its implementation is highly dependent on student readiness, teacher support, and a supportive learning environment. The existence of challenges such as the need for high independence and teacher readiness are factors that need to be considered to ensure that Problem Based Learning can provide maximum benefits for students' learning motivation. The disadvantages of the Problem Based Learning Learning Model are that the problem-solving process through PBL takes longer than traditional learning methods. Students need time to understand the problem, conduct research, discuss, and find solutions.